Examining Mental Health Court Completion: A Focal Concerns Perspective - Dollar, Cindy Brooks (2013)
Sociologists have long-raised concern about disparate treatment in the justice system. Focal concerns have become the dominant perspective in explaining these disparities in legal processing decisions. Despite the growth of problem-solving courts, little research has examined how this perspective operates in nontraditional court settings. This article used a mixed-method approach to examine focal concerns in a mental health court (MHC). Observational findings indicate that gender and length of time in court influence the court's contextualization of noncompliance. While discussions of race were absent in observational data, competing-risk survival analysis finds that gender and race interact to predict MHC termination